6ER-032 Design and implementation of a pharmacy technician training programme to improve outpatient drug dispensing. (2nd March 2018) - Richard, C; Roseau, C; Decottignies, A; Renet, S; Chaumais, MC
Abstract : Background: In most hospital pharmacies, patient drug dispensing is done by pharmacy technicians (PT) under the supervision of a pharmacist. However, PT do not always have all the required knowledge and skills to perform high-quality dispensing. Purpose: Designing and implementing an appropriate training programme for PT to gain all required skills for optimal drug dispensing. Material and methods: The training programme named ACCOMPA-VP was designed using the ADDIE-M method (Analyse, Design, Development, implementation, evaluation and maintenance) combined with the PROFFIteROLE method. 1 The analyse step included four parts (needs, audience, resources and constraints) to describe the existing context and identify patients and PT needs and expectations. It led to the design and development of our adult training programme, combining theory (medical prescription reviewing and patient counselling) and practice (situational exercises according to the PROFFIteROLE method). This training programme has been assessed all along the process. First, the PT skills development was evaluated by the percentage of acquired knowledge and a qualitative analysis of correct answers from each medication order. Then, PT were asked to estimate their self-confidence in performimg optimal drug dispensing. Finally, the quality of the programme was assessed by a PT anonymous survey and a collective feedback. Results: First, a significant improvement in theoretical knowledge (74% to 82% of acquired knowledge, p=0.006) and a decrease in inappropriate counsel;ing (21% to 6%) were observed for all PT (n=9). Second, within 6 months of practice, PT self-confidence throughout the dispensation process was enhanced leading them to gain the abilities to achieve appropriate drug dispensing, especially when it comes to counselling the patient. Finally, all PT felt more comfortable with drug dispensing to patients. They declared having more interactions with the patients and were more likely to detect drug interaction or medication misuse. They assigned a global average grade of 7.7/10, including relational, educational and organisational evaluation. Conclusion: The ACCOMPA-VP training programme permitted the development and reinforcement of PT skills to perform a high-quality dispensation. To maintain the acquired skills, new training sessions will be implemented. Finally, assessment of patients; satisfaction is warranted to demonstrate the overall training benefits. Reference and/or Acknowledgements: 1. http://pharmacie.univ-lille2.fr/innovations-pedagogiques/enseignements-hybrides/pratique-officinale.html (Accessed: 9 October 2017). No conflict of interest